Avoidable mortality in Europe (1980–1997): a comparison of trends. Issue 4 (16th March 2004) - Treurniet, H F; Boshuizen, H C; Harteloh, P P M
Abstract : Study objective: To analyse international variations of trends in "avoidable" mortality (1980–1997). Design: A multilevel model was used to study trends in avoidable and "non-avoidable" mortality and trends by cause of death. Setting: Fifteen countries of the European Union, the Czech Republic, and Hungary. Participants: 19 avoidable causes of death among men and women aged 0–64 years. Mortality and population data were derived from the WHO mortality database; and perinatal mortality rates, from the Health for All statistical database. Main results: Avoidable mortality declined (1980–1997) in all the countries except Hungary. The difference between the trends in avoidable and non-avoidable mortality was small (−2.4% compared with −1.5%) and diminished over time. The largest trend variations between countries are attributable to causes mainly or partly amenable to prevention. For five of the 19 causes of death the international variations diminished over time. Various countries show trends that deviate significantly (p<0.003) from the mean trend. Conclusions: One explanation for the small and diminishing difference between avoidable and non-avoidable mortality is that some large avoidable causes show unfavourable trends. Another possible explanation is that the category of non-avoidable mortality is "polluted" by causes that have become avoidable with time. It is therefore suggested that Rutstein's lists of avoidable outcomes (1976) be updated to enable the appropriate monitoring of healthcare effectiveness. In countries that show unfavourable developments for specific avoidable causes, further research must unravel the causes of these trends.